THE INFLUENCE OF PRODUCT PERCEPTION AND KNOWLEDGE ON INTEREST USE APPLICATION FUND IN METHOD PAYMENT WALLET DIGITAL (USER APPLICATION FUND IN REGENCY KARAWANG) - Adella Adella Pratiwi Ruchyadi; Fajar Ramadhan (SEAN Institute, 2023)
The aim of this research is to describe, analyze and explain the variables involved, as well as to measure the relationship between Perception and Product Knowledge among users of the Dana application. Additionally, the study aims to determine the extent of the partial and simultaneous effects of Perception and Product Knowledge on the Interest in Using the Dana Application. The research adopts a quantitative method, utilizing descriptive and verification analysis. the analytical tools employed is path analysis. the sample consists of 150 respondents, and data is collected through on line questionnaire distribution. The research findings indicate a strong correlation between Perception and Product Knowledge. Additionally, Perception and Product Knowledge have a positive and significant impacts on the Interest in using the Dana Application.